Estudio de los avances de las políticas públicas de salud enfocadas en la rehabilitación de adolescentes con problemas de adicción a sustancias sujetas a fiscalización durante periodo 2021 - Machuca Castillo, Jonathan Andrés (2023)
The present Curricular Integration Work has as its title: "Study of the Progress of public health policies focused on the Rehabilitation of Adolescents with addiction problems to controlled substances during the Period 2021". The general objective of this work is to contrast the progress of public health policies focused on the rehabilitation process of adolescents with addiction problems to controlled substances; with specific goals, such as estimating the impact of rehabilitation programs on adolescents and determining prevention proposals to mitigate addiction problems in adolescents, and establishing whether we fulfilled the appropriate processes to evaluate public health policies. We conducted this research in the city of Loja. And framed the structure of this thesis in the literary analysis based on a conceptual framework in which many sub-topics developed among them: The State, the trajectory and its history, Fundamental rights and guarantees of the State, public policies, its history, types of public policies, public policies focused on the State, adolescence, adolescent offenders, psychotropic substances, addictions, consequences and risks, rehabilitation, types of the reestablishment, in addition to this we also used as a comparative method the following binding Jurisprudence Constitution of Peru, as well as the Jurisprudence of the State of Colombia. The materials and methods used for data collection, such as the survey techniques and five interviews, provided the most accurate and relevant information to support the thesis. As a main conclusion, we established that the public policies conducted are insufficient to mitigate the problem addressed in this research work.